A flood emergency response system based on flood disaster evaluation models - Li Fang; Jianwei Yue; Jiawen Dai; Guobin Ma; Zhuoyuan Yu (2010 18th International Conference on Geoinformatics, 2010)
In this paper we propose an emergency response process based on disaster evaluation models, and a flood emergency response system is developed. Several flood disaster evaluation models are presented which can produce results of house flooded, people affected, and traffic facilities damaged in a flood, and these results are used to make rescue missions with high efficiency in the flood emergency response system.